Perencanaan Fasilitas Wisata Kopi Arabika Sebagai Sarana Edukasi di Kintamani - I Made Artha Mahendra; Agus Kurniawan; I Wayan Wirya Sastrawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
In Indonesia, Arabica coffee is one of the best coffees that is often enjoyed by everyone. Arabica coffee is also not only enjoyed, but starting from cultivation to becoming the best coffee beans in Indonesia and even abroad. Until now, coffee biscuits have become very popular among the public because they have great opportunities and high competitiveness in national and even international marketing. Of all types of Arabica coffee in Indonesia and even internationally, Kintamani Arabica coffee beans have a unique difference when compared to other types of coffee, Kintamani Arabica coffee has its own competitive advantage. Kintamani Arabica coffee comes from an area with a minimum elevation of approximately 900 meters above sea level. However, in its current development, Arabica coffee is still lacking in education, both in terms of Arabica coffee cultivation and in terms of presentation. Because the unique taste needs to be packaged as well as possible so that the characteristic taste of Arabica coffee is not lost. Therefore, the purpose of this plan is to develop Arabica coffee tourism as a means of education for both the community, the public and foreign countries. The research method used is a qualitative method to analyze theory and collect data. The results of the research are in the form of programs and concepts for planning and designing Arabica coffee tours as a means of education.